PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP PEMAHAMAN KONSEP PADA MATERI WUJUD ZAT DAN PERUBAHANNYA KELAS IV DI SDN 17 SINGKAWANG - Fitri, Fitri Dwi Astuti; Andika Kusuma Wijaya; Safrihady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low ability to understand students' concepts that occurs in class IV and the use of media in learning is also needed so that students are more interested in learning. The aim of this research is to find out how much influence the discovery learning model assisted by audio-visual media has on class IV students' conceptual understanding at SDN 17 Singkawang. This research is a quantitative research using quasi-experimental design with a nonequivalent control group design. The sampling used in this research was nonprobability sampling with purposive sampling type. So the sample for this research is class IV B as the experimental class with a total of 28 students and class IV C as the control class with a total of 28 students so that the sample in this research is 56 students. The instrument used is a test in the form of essay questions. The research results show that testing the hypothesis using a two-sample t test shows that the value of > is 4.43 > 1.706, so Ha is accepted and H0 is rejected. With the results, there are differences in the conceptual understanding of class IV students who use the discovery learning learning model assisted by audio-visual media with those of classes who use the direct model at SDN 17 Singkawang. then the Effect Size test obtained a value of 0.96 with high criteria. So in this research, the use of the discovery learning model assisted by audio-visual media has a high influence on students' conceptual understanding. The effect size results are at a value of 0.96, in the range 0,8<ES≤1,30.